2013
DOI: 10.1007/s13593-013-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological practices for sustainable agriculture. A review

Abstract: International audienceThe forecasted 9.1 billion population in 2050 will require an increase in food production for an additional two billion people. There is thus an active debate on new farming practices that could produce more food in a sustainable way. Here, we list agroecological cropping practices in temperate areas. We classify practices according to efficiency, substitution, and redesign. We analyse their advantages and drawbacks with emphasis on diversification. We evaluate the potential use of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
622
1
33

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 865 publications
(660 citation statements)
references
References 126 publications
(151 reference statements)
4
622
1
33
Order By: Relevance
“…In sustainable/organic farming systems, ASC represent a powerful tool for farmers to positively influence the agro-ecosystem by promoting the whole soil-plant system equilibrium in space and time (Kremen & Miles, 2012;Canali, 2013;Wezel et al, 2014). ASC may have impact on soil fertility (Thorup Montemurro et al, 2013), occurrence of weeds (Bàrberi, 2002;Hayden et al, 2012), diseases and pests (Masiunas, 1998;Patkowska et al, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In sustainable/organic farming systems, ASC represent a powerful tool for farmers to positively influence the agro-ecosystem by promoting the whole soil-plant system equilibrium in space and time (Kremen & Miles, 2012;Canali, 2013;Wezel et al, 2014). ASC may have impact on soil fertility (Thorup Montemurro et al, 2013), occurrence of weeds (Bàrberi, 2002;Hayden et al, 2012), diseases and pests (Masiunas, 1998;Patkowska et al, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Some authors address production-oriented agriculture issues without distinguishing between the two forms of ecological modernisation (Godfray et al 2010;Wezel et al 2013). In line with Horlings and Marsden (2011), we argue that this is problematic for at least two main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…More concretely, such scholars have frequently suggested that organic/agro-ecological food production is desirable and necessary (e.g., Boonstra and Joosee, 2013;Kallis, 2011). This type of agriculture integrates ecological processes into farming practices instead of relying on fertilizers, pesticides or genetic modifications of organisms (see Gomiero et al, 2011 andWezel et al, 2014: 3 for research reviews on the performance of organic agriculture). Organic agriculture does not use synthetic nitrogen fertilizer, which is responsible for 75% of all CO2 emissions in conventional farming (Haas et al, 1995), uses up to 75% less fossil fuels (LaSalle and Hepperly, 2008: 4) and produces higher rates of soil carbon (instead of emitting it to the atmosphere as in conventional farming).…”
Section: Satisfying the Global Need For Foodmentioning
confidence: 99%